2015
DOI: 10.12691/education-3-8-12
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of Faculty Members' Organizational Commitmentin the Kingdom of Saudi Arabia

Abstract: The present study utilizes the Meyer and Allen three-component model of organizational commitment to measure commitment among faculty members in Saudi Arabia. The study further investigates the relationship between the faculty's demographic variables (gender, academic rank, college cluster, years of experience, and nationality) and their organizational commitment. A survey research design was used to measure 185 faculty members' commitment to their organizations. This study's results demonstrate high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
(37 reference statements)
3
11
1
Order By: Relevance
“…The findings of a previous study on effect of organizational climate on organizational commitment among faculty of nursing in Egypt indicated that most faculty had a moderate level of organizational commitment [ 19 ]. The findings of the current study are dissimilar with the findings of an empirical investigation of faculty members’ organizational commitment in Saudi Arabia, which revealed that faculty had high level (73.4%) and moderate level (26.0%) of commitment for overall organizational commitment [ 20 ]. Another study on assessment of work environment and employee’s commitment in college of nursing in Saudi Arabia also revealed that the respondents had high commitment scores (61.2%), and moderate commitment scores (38.8%) [ 21 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of a previous study on effect of organizational climate on organizational commitment among faculty of nursing in Egypt indicated that most faculty had a moderate level of organizational commitment [ 19 ]. The findings of the current study are dissimilar with the findings of an empirical investigation of faculty members’ organizational commitment in Saudi Arabia, which revealed that faculty had high level (73.4%) and moderate level (26.0%) of commitment for overall organizational commitment [ 20 ]. Another study on assessment of work environment and employee’s commitment in college of nursing in Saudi Arabia also revealed that the respondents had high commitment scores (61.2%), and moderate commitment scores (38.8%) [ 21 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The current study also revealed that position contributed significantly to the prediction of low to moderate level of organizational commitment. The finding of the current study is consistent a previous study of Saudi Arabia which showed that academic rank was found to be significantly related to organizational commitment [ 20 ]. The supportive argument related to association between position and organizational commitment is that at a higher position, opportunities and responsibilities also increase.…”
Section: Discussionsupporting
confidence: 92%
“…'Workplace spirituality' relates the desires of employees to live integrated, holistic lives, including recognition and acceptance of their spirituality in the work context (Aravamudhan & Khrishmaveni, 2014). By analysing literature (see BinBakr & Ahmed, 2015;Mohamed & Ruth, 2016;Wainaina et al, 2014) three distinct components of workplace spirituality emergesense of meaning, sense of purpose and a sense of community or connectedness with others. For the sake of this study, workplace spirituality can be explained as a dynamic process http://www.sajhrm.co.za Open Access…”
Section: Workplace Spiritualitymentioning
confidence: 99%
“…On the other hand, age followed by gender appeared to be one of the most significant determinants for the normative commitment and the least determinant factor for the affective commitment (Wolowska, 2014). A very small number of studies have examined the relation between nationality and organizational commitment, the work by BinBakr and Ahmed (2015) representing one of the exceptions.…”
Section: Rewardsmentioning
confidence: 99%